گوتاری ڕۆمانی کوردی لە نێوان ساڵانی ١٩٩٢-٢٠٠٢ - ئهمین, محهمهد دلێر; حسين, هیوا کهریم (Sulaimani Journal for Humanities, 2021)
Narrative discourse in novel attempts to construct narrative structure as a complete entity which shows the novel discourse. Discourse does not analyze the novel constructive structure, but it focuses on historical context and the events that have roles in producing novel. In other word, it attempts to see novel as a humanitarian experience. The current study, “Kurdish Novel Discourse: 1992 to 2003”, is an attempt to find out and study the novel discourse of those years as a part of Kurdish general discourse. The study consists of an introduction and two main sections. In the introduction we shed light on novel as a new genre of prose and its influence in the society. In the first section, we have highlighted the discourse of novel titles during this period, especially those changes occurred in technical and content aspect. Regarding the second section, we analyzed Kurdish novel discourse according to Gerard Genet, especially from time, organization, and period aspect in which we highlighted a number of dimensions of Kurdish novel. Finally, we presented some points as the study conclusions and organized the reference list according to Harvard style.